(untitled) (International Conference on Computers in Education, 2016)
We currently utilize the Moodle learning management system for teachers and students who participate in the course ‘College of Liberal Arts and Sciences’ at Kobe University in Japan. Digital textbooks, reports, quizzes and questionnaires in this course were administered using Moodle. In this paper, we proposed to use quizzes to measure and evaluate those digital textbooks recorded on Moodle. At the beginning of our study, we examined the questions that students got lower scores, and then we found the related teaching materials of digital textbooks and feedback to the teachers in order to improve the content of these digital textbooks.